1994
DOI: 10.1182/blood.v83.12.3697.bloodjournal83123697
|View full text |Cite
|
Sign up to set email alerts
|

RANTES- and interleukin-8-induced responses in normal human eosinophils: effects of priming with interleukin-5

Abstract: We report that responses of normal human eosinophils toward the chemokines RANTES and interleukin-8 (IL-8) are modulated and upregulated by priming with IL-5. In a modified Boyden chamber assay, we studied migratory responses toward the members of the chemokine family RANTES, monocyte chemotactic protein-1 (MCP-1), and macrophage inflammatory protein-1 alpha (MIP-1 alpha) (C-C subfamily), and IL-8, platelet factor-4 (PF-4), and neutrophil-activating peptide-2 (NAP-2) (C-x-C subfamily). These chemokines were al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Results of another study in vitro of cytokine‐induced eosinophil transendothelial cell migration showed that Rantes alone induced the migration of eosinophils across an endothelial cell barrier, and that this action was maximized by pretreatment of the eosinophils with IL5 (25). Rantes also induces mild activation of eosinophils in vitro, as measured by the release of cationic protein, superoxide production, and the induction of hypodensity (26). Interleukin‐5 is a potent chemoattractant for eosinophis and an activator of eosinophil functions (27).…”
Section: Discussionmentioning
confidence: 99%
“…Results of another study in vitro of cytokine‐induced eosinophil transendothelial cell migration showed that Rantes alone induced the migration of eosinophils across an endothelial cell barrier, and that this action was maximized by pretreatment of the eosinophils with IL5 (25). Rantes also induces mild activation of eosinophils in vitro, as measured by the release of cationic protein, superoxide production, and the induction of hypodensity (26). Interleukin‐5 is a potent chemoattractant for eosinophis and an activator of eosinophil functions (27).…”
Section: Discussionmentioning
confidence: 99%